THE ROLE OF GREEN TRUST IN MEDIATING THE RELATIONSHIP BETWEEN GREEN PERCEIVED VALUE AND GREEN PURCHASE INTENTION OF E-COMMERCE BEAUTY PRODUCTS - Wulan Nur Wijayanti; Edwin Zusrony; Pindo Asti; Gibson Manalu (ITB AAS Indonesia Surakarta, 2026)
This study investigates the impact of Green Perceived Value on Green Purchase Intention mediated by Green Trust among Generation Z consumers aged 18-25 living in Semarang Regency who purchase skincare on e-commerce platforms. The sampling technique used a purposive sampling method and obtained 70 respondents. This study used a quantitative study using SEM-PLS. The data collection technique used a questionnaire and was measured using a Likert scale of 1-5. Based on the results of the quantitative investigation of Structural Equation Modeling (SEM), the response results showed a significant positive relationship between Green Perceived Value activities on Green Purchase Intention. Furthermore, the Green Trust variable was able to mediate the influence of Green Perceived Value on Green Purchase Intention. In addition, Green Trust was found to have a positive impact on Green Purchase Intention. These findings emphasize the importance of the Green Perceived Value strategy in encouraging Green Purchase Intention, and skincare companies can focus more on increasing Green Perceived Value and Green Trust to encourage Green Purchase Intention.